2020
DOI: 10.1038/s41420-020-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits IL-1β secretion via impairment of NLRP3 inflammasome in keratinocytes: implications for preventing the development of psoriasis

Abstract: Psoriasis is a systemic inflammatory disease significantly associated with comorbidities including type 2 diabetes mellitus (T2DM). Metformin is utilized as a first-line agent for treating T2DM. Although metformin reportedly inhibits mature IL-1β secretion via NLRP3 inflammasome in macrophages of T2DM patients, it remains unclear whether it affects skin inflammation in psoriasis. To test this, we analysed normal human epidermal keratinocytes (NHEKs), a major skin component, stimulated with the key mediators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Regulation of NLRP3 inflammasome activation could represent a target for future pharmacologic interventions employing SLURP-1. This is especially interesting in chronic inflammatory skin and allergic diseases ( 107 ) that reportedly are stress-sensitive and involve NLRP3 inflammasome activation such as psoriasis ( 108 ), contact hypersensitivity ( 109 ) or asthma ( 110 ). In fact, in a microarray analysis employing the Affymetrix Mouse Genome 430A 2.0 Array that we had performed in another project ( 6 ), we had previously observed the as yet unreported upregulation of Asc (1.280-fold) and Casp1 (0.397-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of NLRP3 inflammasome activation could represent a target for future pharmacologic interventions employing SLURP-1. This is especially interesting in chronic inflammatory skin and allergic diseases ( 107 ) that reportedly are stress-sensitive and involve NLRP3 inflammasome activation such as psoriasis ( 108 ), contact hypersensitivity ( 109 ) or asthma ( 110 ). In fact, in a microarray analysis employing the Affymetrix Mouse Genome 430A 2.0 Array that we had performed in another project ( 6 ), we had previously observed the as yet unreported upregulation of Asc (1.280-fold) and Casp1 (0.397-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes are suspected to play a pathogenic role in the complications of diabetes, in a host of neurodegenerative disorders, in autoimmune disorders including rheumatoid arthritis, and in periodontal disease [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Inflammasomes contribute to the pathogenesis of chronic skin disorders such as psoriasis and acne [ 20 , 21 , 22 , 23 ]. They have also been linked to asthma and allergic inflammation [ 24 , 25 , 26 , 27 ].…”
Section: Mechanisms Involved In the Priming And Activation Of Inflmentioning
confidence: 99%
“…First, AMP-activated protein kinase has been shown to exert anti-inflammatory effects in macrophages [43]. It has also been reported that metformin treatment results in decreased inflammatory markers and cytokines such as tumor necrosis factor alpha (TNF-α) and IL-1β [44]. In the keratinocytes corresponding to the epidermal tissue, it has been found that metformin reduces cell proliferation through the mitogen-activated protein kinase (MAPK) signaling pathway [45].…”
Section: Psoriasismentioning
confidence: 99%